Helping to stop doctors becoming complicit in torture. (25th February 2010) - Polatin, Peter B; Modvig, Jens; Rytter, Therese
Abstract : A new UN resolution should help doctors to follow their consciences when confronted with torture say Peter Polatin, Jens Modvig, and Therese Rytter